Robust skin diseases detection and classification using deep neural networks - Albawi, Saad; Amer Abbas, Yasir; Almadany, Yasser (International Journal of Engineering and Technology, 2019)
Since from last decade, there is significant growth in the design of Computer-Aided Diagnosis (CAD) Systems using image processing. There are different images processing steps on which the efficiency of such CAD systems relies such as image pre-processing, image segmentation, feature extraction, and classification. There are recent attempts by proposing novel algorithms in either of CAD model steps, however designing robust, useful and accurate CAD system for skin diseases' detection is still challenging research problem. In this paper, unique skin disease identification was proposed for three types of skin diseases such as Melanoma, Nevus, and Atypical. For pre-processing, an adaptive filtering method was designed to remove unwanted noisy areas from the input skin image. For segmentation, adaptive region growing technique was developed for efficient localization and region of interest (ROI) extraction of disease area. This segmentation adaptively selects the next region to grow for accurate lesion segmentation. For feature extraction, we exploited a hybrid feature extraction method composed of 2dimensions discrete wavelet transform (2D-DWT), geometric and texture features. The deep learning algorithm performs the classification. Convolutional neural networks (CNN) is used for the efficient prediction of skin disease. The experimental analysis is performed usingInternational Skin Imaging Collaboration (ISIC) dataset. The proposed method can classification the skin diseases with accuracy of 96.768%. The results obtained showing that the proposed method outperformed the state-of-art techniques.
Keywords: Lesions; Skin Disease; CAD; Segmentation; Deep Learning; Melanoma; Nevus.